1998
DOI: 10.1016/s0735-1097(98)80282-9
|View full text |Cite
|
Sign up to set email alerts
|

Congestive heart failure in the community: changes in incidence and survival over a 10-year period

Abstract: Objective: To compare the incidence of congestive heart failure and the survival in patients with congestive heart failure in Rochester, Minn, in 1981 with that observed in 1991.Methods: Population-based, descriptive epidemiological study with ecological and individual level comparisons over time. Olmsted County, Minnesota, where the Rochester Epidemiology Project provides passive surveillance of the population for health outcomes. All 248 patients fulfilled the Framingham criteria, 107 patients presenting wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
1
3

Year Published

2000
2000
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 0 publications
1
37
1
3
Order By: Relevance
“…These clinics do not accept patients who are cognitively impaired or are unable to attend appointments regularly, which may explain the mean age of the patients (65 years), and is considerably younger than the average age of 75 years in epidemiological studies (25,31,32). In Montreal, in 1999, 85% of the hospitalizations for CHF were for people 65 years of age and older (33).…”
Section: Discussionmentioning
confidence: 99%
“…These clinics do not accept patients who are cognitively impaired or are unable to attend appointments regularly, which may explain the mean age of the patients (65 years), and is considerably younger than the average age of 75 years in epidemiological studies (25,31,32). In Montreal, in 1999, 85% of the hospitalizations for CHF were for people 65 years of age and older (33).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the main findings concerning CHF in this age class derive from studies conducted in the United States; the Framingham study, 6) the Cardiovascular Health study, 12) the New Haven Connecticut cohort of the Established Population for Epidemiological Studies of the Elderly program, 13) and the experiences of Cowie, et al 10) and Senni, et al 20) have made the greatest contribution to this topic. In Europe, the data on CHF in the elderly derive from the Rotterdam Study 13) and in part from the non-population-based experience that Cowie, et al 21) reported among general practitioners of West London.…”
Section: Discussionmentioning
confidence: 99%
“…This is a quite different finding from that reported by the Framingham investigators in 1993, 9 who studied patients developing heart failure in the period 1948 to 1988, and by the Rochester investigators, who studied patients in the period 1981 to 1991. 11 In both of these studies, no temporal change in prognosis was identified. Therefore, it is clearly tempting to suggest that our more encouraging observations, from an era when ACE inhibitors have become more widely used, reflect a true improvement in survival, consequent on better treatment.…”
Section: Macintyre Et Al Improving Survival From Heart Failurementioning
confidence: 93%
“…The Rochester Epidemiology project has also described the prognosis in 107 patients presenting to associated hospitals with new-onset heart failure in 1981 and in 141 patients presenting in 1991. 11 The median follow-up in these cohorts was 1061 and 1233 days, respectively. The mean age of the 1981 patients was 75 years, rising to 77 years in 1991.…”
Section: Macintyre Et Al Improving Survival From Heart Failurementioning
confidence: 99%